Regularity Criterion for Weak Solutions to the Navier-Stokes Equations in Terms of the Gradient of the Pressure. (30th November 2008) - Fan, Jishan; Ozawa, Tohru
Abstract : We prove a regularity criterion∇ π ∈ L 2 / 3 ( 0, T ; BMO ) for weak solutions to the Navier-Stokes equations in three-space dimensions. This improves the available result withL 2 / 3 ( 0, T ; L ∞ ) .